Analyzing cumulative effects from human development on reindeer habitat in Sweden - Driedger, Erika (2014)
Rangifer sp., also called reindeer or caribou, are characterized by their seasonal movements over the landscape, making them a good indicator for cumulative disturbance effects caused by human developments. This study integrates indigenous ecological knowledge from reindeer herders in northern Sweden to identify current proportions of developed reindeer range and to assess cumulative impacts of development on reindeer husbandry. Mapping revealed the study area as 16.3 % developed, within which 18.4 % of high-use areas were developed. Applying a minimum buffer distance from literature around all developments suggested impacts of 58.7 % on the winter range and 78.6 % on high-use areas. Without buffering forest harvest, impacts were 24.7 % and 24.2 % respectively. A resource selection function with herder-defined high-use area data highlighted the challenge and importance of integrating both social and ecological factors into future cumulative effects analysis.